Life history strategy and adult and larval behavior of Macrodiplosis selenis (Diptera: Cecidomyiidae), a species that induces leaf‐margin fold galls on deciduous Quercus (Fagaceae). Issue 4 (26th July 2015) - Kim, Wanggyu; Matsunaga, Kiyoko; Gyoutoku, Naohisa; Matsuo, Kazunori; Minami, Tsuneo; Yukawa, Junichi
Abstract Life historical, behavioral and ecological traits of Macrodiplosis selenis, which induces leaf‐margin fold galls on Quercus serrata, Q. mongolica and Q. dentata (Fagaceae) in Japan and South Korea, were studied. Daily activity and larval development indicate that M. selenis is a diurnal and univoltine gall midge. In April, females lay their eggs both on upper and under surfaces of fresh leaves. The duration of the egg stage varies from 5 to 9 days, depending on daily temperatures. Hatched larvae crawl to the upper surface of the leaf margin, where they start to induce galls. Larvae become full‐grown in October, drop to the ground in November and overwinter in cocoons on the ground, while larvae of congeners mature in May and drop to the ground in June. A relatively long period of the second larval stadium from July to October on the host trees seems to be effective for M. selenis in avoiding summer mortalities caused by predation and aridity on the ground and by ectoparasitoids that attack mature larvae or pupae on the host leaves. The spatial distribution pattern of M. selenis leaf galls is contagious and the mean gall density per leaf is significantly correlated with the mean crowding. This study adds new insights of life history strategy and adult and larval behavioral pattern to the ecological knowledge of gall midges, and these kinds of information are essential for further studies of M. selenis population dynamics and interactions with other Quercus‐associated herbivores.